Thalamic inflammation after brain trauma is associated with thalamo-cortical white matter damage - Scott,G; Hellyer,PJ; Ramlackhansingh,AF; Brooks,DJ; Matthews,PM; Sharp,DJ (Journal of Neuroinflammation, 2015)
BackgroundTraumatic brain injury can trigger chronic neuroinflammation, which may predispose to neurodegeneration. Animal models and human pathological studies demonstrate persistent inflammation in the thalamus associated with axonal injury, but this relationship has never been shown in vivo.FindingsUsing [11C]-PK11195 positron emission tomography, a marker of microglial activation, we previously demonstrated thalamic inflammation up to 17 years after traumatic brain injury. Here, we use diffusion MRI to estimate axonal injury and show that thalamic inflammation is correlated with thalamo-cortical tract damage.ConclusionsThese findings support a link between axonal damage and persistent inflammation after brain injury.